KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBINAAN KOMPETENSI PEDAGOGIK GURU DI SMANEGERI 1 UNGGUL DARUL IMARAH KABUPATEN ACEH BESAR - Sri Rahmiq; Nurussalami Nurussalami; Devi Yani (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Data collectiontechniques using interviews, observation, and documentation. The results of thisstudy indicate that the leadership style of the headmaster of SMA Negeri 1 DarulImarah has two leadership styles namely, charismatic leadership style anddemocratic leadership style. While the teacher pedagogical competencydevelopment model by the head of Neegri 1 Darul Imarah High School uses themodel of class supervision, workshops, procurement of school meetings, andseminars or training. The obstacles of the head of SMA Negeri 1 Darul Imarah indeveloping teacher pedagogical competence are, the lack of teacher preparation inmaking learning tools, and there are some teachers who lack discipline inattending meetings.